Effects of extract solution from magnesium alloys supplemented with different compositions of rare earth elements on in vitro epithelial and osteoblast progenitor cells - Nie, Sheng; Chen, Jiakai; Liu, Chen; Zhou, Chenhui; Zhao, Jikuang; Wang, Zhepei; Sun, Jie; Huang, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Magnesium alloys (Mg-alloys) have gained significant attention in recent years as a potential bioactive material for clinical applications. The incorporation of rare earth elements (REEs) into Mg-alloys has been of particular interest due to their potential to improve both mechanical and biological properties. Although there are diverse results in terms of cytotoxicity and biological effects of REEs, investigating the physiological benefits of Mg-alloys supplemented with REEs will help in the transition from theoretical to practical applications. Methods: In this study, two culture systems were used to evaluate the effects of Mg-alloys containing gadolinium (Gd), dysprosium (Dy), and yttrium (Y): human umbilical vein endothelial cells (HUVEC) and mouse osteoblastic progenitor cells (MC3T3-E1). Different compositions of Mg-alloys were assessed, and the effects of the extract solution on cell proliferation, viability, and specific cell functions were analyzed. Results: Within the range of weight percentages tested, the Mg-REE alloys did not exhibit any significant negative impacts on either cell line. Interestingly, moderate compositions (Mg-1.5Gd-1.5Dy-0.825Y-0.5Zr and Mg-2Gd-2Dy-1.1Y-0.5Zr) demonstrated a tendency to enhance osteoblastic activity and promote the vascularization process in both HUVEC and MC3T3-E1 cell lines. Discussion: The results of this study provide valuable insights into the potential benefits of REE-supplemented Mg-alloys for clinical applications. The observed enhancement in osteoblastic activity and promotion of vascularization processes suggest that optimizing the compositions of REEs in Mg-alloys could lead to the development of novel, more effective bioactive materials. Further investigations are required to understand the underlying mechanisms and to refine the alloy compositions for improved biocompatibility and performance in clinical settings.